2003
DOI: 10.1046/j.1365-2559.2003.01600.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HER‐2/neu gene and protein in salivary duct carcinomas of parotid gland as revealed by fluorescence in‐situ hybridization and immunohistochemistry

Abstract: In immunohistochemistry, over-expression of HER-2/neu protein was identified as distinct membrane staining in most carcinoma cells in all our salivary duct carcinoma cases, while only four cases revealed an amplification of HER-2/neu gene by means of FISH analysis. Both amplified and non-amplified salivary duct carcinomas with strong immunohistochemical staining for HER-2/neu protein were associated with poor clinical outcome for the patients. Apparently, HER-2/neu protein over-expression could also be control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(103 citation statements)
references
References 37 publications
10
92
1
Order By: Relevance
“…Only in one tumor specimen was the overexpression linked to a gene amplification. These observations are in concordance with a recent study by Etges et al 30 It is noteworthy that patients negative for HER-2/neu expression clinically also had an unfavorable prognosis, an observation that was reported recently by Skalova et al 31 for a small study group.…”
Section: Table 4 Prognostically Significant Factors In Sdc Clinical Csupporting
confidence: 93%
“…Only in one tumor specimen was the overexpression linked to a gene amplification. These observations are in concordance with a recent study by Etges et al 30 It is noteworthy that patients negative for HER-2/neu expression clinically also had an unfavorable prognosis, an observation that was reported recently by Skalova et al 31 for a small study group.…”
Section: Table 4 Prognostically Significant Factors In Sdc Clinical Csupporting
confidence: 93%
“…A number of previous studies demonstrated that HER-2/neu and p53 expression are statistically associated with SDC survival rates (3,(15)(16)(17)(18)(19)(20). However, in the present study, the protein expression levels of HER-2/neu, AR, Ki-67, p16 and p53 did not correlate with prognosis, although HER-2/neu, AR and p16 demonstrated a positive expression rate of >50%, which may contribute to the diagnosis for SDC.…”
Section: A B C D Econtrasting
confidence: 80%
“…The HER2 gene encodes for a receptor tyrosine kinase often amplified and overexpressed in SDC (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Using FISH, we detected HER2 gene amplification in 8 of 27 cases (30%).…”
Section: Clinical Characteristics Of the Cohortmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17]. In contrast to breast carcinoma, SDC are consistently negative for estrogen-a and progesterone receptors, whereas the expression of androgen receptor (AR) is observed in the majority of cases (18).…”
Section: Introductionmentioning
confidence: 99%